2021
DOI: 10.1111/padr.12437
|View full text |Cite
|
Sign up to set email alerts
|

Where Do People Live Longer in Russia in the 21st Century? Life Expectancy across Urban and Rural areas

Abstract: The twenty‐first century marked the beginning of rapid health improvements in Russia. In the late 2000s and the 2010s, there was already a moderate decrease in inter‐oblast mortality disparities, with the exception of the growing life expectancy (LE) advantage of Moscow and Saint Petersburg. We have used newly available data to explore LE changes from 2003–2005 to 2015–2017 and determinants of LE differences across settlements of different types and population sizes. We distinguished between three major segmen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 25 publications
0
5
0
Order By: Relevance
“…Previous studies in other countries as well as those focused on Russia revealed that measurable reductions in mortality rates are detected more frequently in larger cities compared to smaller towns and rural settlements. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previous studies in other countries as well as those focused on Russia revealed that measurable reductions in mortality rates are detected more frequently in larger cities compared to smaller towns and rural settlements. 11 , 12 …”
Section: Discussionmentioning
confidence: 99%
“…Significant reductions in mortality rates were observed primarily amongst those residing in the larger cities compared to rural oblasts and were more likely to be due to reductions in external causes rather than related to a specific impact on cerebrovascular diseases. 11 , 12 …”
Section: Introductionmentioning
confidence: 99%
“…The study period was characterized by a significant decline in mortality. Life expectancy began to gradually increase from the mid-2000s onwards, initially in the capital and in the largest cities (Shchur, 2019;Shchur et al, 2021). As a result, a substantial geographic and hierarchical disparity in mortality had emerged by 2010 (Timonin et al, 2020).…”
Section: The Variations In Excess Mortality By Settlement Sizementioning
confidence: 99%
“…Given that urban heat island effects are most pronounced in densely populated urban areas, it was anticipated that the largest increases in death rates would be observed in the largest cities and their surrounding agglomerations. Conversely, "core-periphery" inequalities, which have been linked to substantial spatial disparities in life expectancy, particularly in Russia by the end of the first decade of the 21st century (Shchur, 2019;Shchur et al, 2021), might have reversed the expected outcomes. During that period, rapid advancements in public health and health-conscious behavioural changes in Russia primarily occurred in the most populated urban areas, and had limited impacts on peripheral cities and rural areas.…”
Section: Introductionmentioning
confidence: 99%
“…Mortality studies analyzing a lower administrative-territorial level are rather scarсe in Russia. It is only in recent years that publications on mortality at the municipal level have begun to appear nationwide: mortality in the municipal districts of Russia (Timonin et al 2020), in «million plus» cities (Shchur 2018), regional capitals (Shchur, Timonin 2020), and large and small cities (Shchur et al 2021). The level and structure of mortality in Moscow and other megacities of the world were compared (Andreev et al 2016).…”
Section: Introductionmentioning
confidence: 99%